1952
DOI: 10.1039/jr9520003129
|View full text |Cite
|
Sign up to set email alerts
|

599. Properties of ion-exchange resins in relation to their structure. Part IV. Swelling and shrinkage of sulphonated polystyrenes of different cross-linking

Abstract: Ion-exchange Resins in ReLatiogz to Strzbct z m . Pad I V . 3 129 599. Pyoperties of Pon-exch,ange Resins in Relation to Their Xtructure. Swelling und Xhrinkage of Xulphonated Polystyrenes of Pa,rt I V.* Different Crosslinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

1954
1954
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(57 citation statements)
references
References 0 publications
2
55
0
Order By: Relevance
“…Swelling occurs when the resin traps a cation with a larger hydrated equivalent ionic volume, expanding its crosslinked structure [31,32]. The hydrated ionic volume is defined as the volume occupied by an ion when it is surrounded by water and it is proportional to its hydrated radius.…”
Section: Resin Propertiesmentioning
confidence: 99%
“…Swelling occurs when the resin traps a cation with a larger hydrated equivalent ionic volume, expanding its crosslinked structure [31,32]. The hydrated ionic volume is defined as the volume occupied by an ion when it is surrounded by water and it is proportional to its hydrated radius.…”
Section: Resin Propertiesmentioning
confidence: 99%
“…In order to calculate the amount of lysine adsorbed by the resin, it was necessary to know the volume of liquid held between the resin particles. This was determined by a centrifuge method (Pepper, Reichenberg & Hale, 1952). It was found that the total amount of liquid taken up by the resin (including the liquid between the particles of resin) was dependent on the pH of the buffer, but the amount of liquid removed by centrifuging remained almost constant (1.8 ml./g.…”
Section: Aamentioning
confidence: 99%
“…20) After measurement of the weight of microspheres in wet state, the microspheres were dried at 60°C for 24 h and the weight was re-measured. The degree of water uptake was calculated with the following equation:…”
Section: Scanning Electron Microscope (Sem) Observationmentioning
confidence: 99%